CeO2 hollow nanospheres synthesized by a one pot template-free hydrothermal method and their application as catalyst support1. Issue 72 (6th August 2015) - Xu, Yuanmei; Zhang, Yiwei; Zhou, Yuming; Xiang, Sanming; Wang, Qianli; Zhang, Chao; Sheng, Xiaoli
<x xml:space="preserve">Abstract</x> Uniform ceria hollow nanospheres composed of ceria nanocrystals have been synthesized via a simple one-step hydrothermal method without using any template.